E-Comic Learning Media Based Problem Based Learning In Subject of Linear Equation System - Muhammad Farid Nasrulloh; Siti Hanik; Wisnu Siwi Satiti (Hipotenusa : Journal of Mathematical Society, 2020)
This study aims to learn the feasibility of e-comic media  in MTsN 12 Jombang. The method of this research is Research and Development (RD). The development model used is the ADDIE development model with stages: analysis (analysis), design (design), development (development), implementation (implementation), and evaluation (evaluation). The subjects of this research  were students of class VII D of MTsN 12 Jombang. The research instruments used in data collection were (1) questionnaire sheets and (2) students' response results. The results showed that the validity of the learning media obtained was based on the validation of the material experts showed 4.2 with a valid category, assessment of the validation of the material experts showed 4.8 with a very valid category, validation of the existing media experts showed 4.53 with a very valid category and participant responses students there are 94% with the category of strongly agree.